INTEGRASI PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH DENGAN LINGKUNGAN UNTUK MENINGKATKAN MINAT BELAJAR BIOLOGI - Riskey Oktavian; Riantina Fitra Aldya (Inteligensi : Jurnal Ilmu Pendidikan, 2020)
This study aims to determine whether the integration of learning media with the environment is able or not to increase student interest in learning. This research uses meta-analysis-data in the form of descriptive explorative qualitative, which is related to learning media and the environment. Data is collected from various secondary data, which is combined and analyzed by calculating the same percentage of findings for similar problems. The results show that this integration can increase student interest in learning, especially when learning about Science at the Botanical Gardens School, which is characterized by increasing positive behaviors and feelings, also increasing attention, and involvement of students in learning.